1997
DOI: 10.1046/j.1471-4159.1997.68010344.x
|View full text |Cite
|
Sign up to set email alerts
|

Key Residues Defining the μ‐Opioid Receptor Binding Pocket: A Site‐Directed Mutagenesis Study

Abstract: Structural elements of the rat 1.t-opioid receptor important in ligand receptor binding and selectivity were examined using a site-directed mutagenesis approach. Five single amino acid mutations were made, three that altered conserved residues in the~8, and K receptors (Asn 15°to Ala, His297 to Ala, and Tyr326 to Phe) and two designed to test for~i/8 selectivity (lie198 to Val and Va1202 to lie). Mutation of His297 in transmembrane domain 6 (TM6) resulted in no detectable binding with [3H]DAMGO (3H-iabeied c-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 26 publications
7
109
0
Order By: Relevance
“…It had previously been hypothesized that a positively charged amino substituent would form a salt bridge with a negatively charged aspartate residue, which is highly conserved within the third transmembrane domain of the opioid receptor (Surratt et al, 1994;Mansour et al, 1997;Lu et al, 2001). The lack of such functionality within the tricyclic skeleton makes it unlikely that these ionic interactions are stabilizing salvinorin A in a manner similar to that of other nitrogenous opioids.…”
Section: B Proposed Binding Interactions With -Opioid Receptorsmentioning
confidence: 99%
“…It had previously been hypothesized that a positively charged amino substituent would form a salt bridge with a negatively charged aspartate residue, which is highly conserved within the third transmembrane domain of the opioid receptor (Surratt et al, 1994;Mansour et al, 1997;Lu et al, 2001). The lack of such functionality within the tricyclic skeleton makes it unlikely that these ionic interactions are stabilizing salvinorin A in a manner similar to that of other nitrogenous opioids.…”
Section: B Proposed Binding Interactions With -Opioid Receptorsmentioning
confidence: 99%
“…39 , 40 The residues from the binding pocket, essential for ligand binding, are mostly conserved across the ORs and include Asp(3.32), Tyr(3.33), Lys(5.39), Phe(5.47), Trp(6.48), Ile(6.51), His(6.52), Ile(6.53), Ile(7.39), and Tyr(7.43). [41][42][43][44][45][46][47][48][49][50] Binding determinants for small alkaloids (morphine, codeine) reside in TMs 5 -7. 51 Variable binding pocket residues confer selectivity.…”
Section: Experimental Studies Of Receptor-ligand Interactionsmentioning
confidence: 99%
“…The aliphatic 6-hydroxyl group was first thought to interact with Tyr 326 (Mansour et al, 1997) or with Asn 230 (Pogozheva et al, 1998). Our group showed that the potency of morphine increased when this Asn 230 residue was replaced by a hydrophobic amino acid (Pil and Tytgat, 2001).…”
Section: Discussionmentioning
confidence: 99%